Analisis Faktor Hiperbilirubinemia pada Bayi Di RSUD dr. Gunawan Mangunkusumo - Primasdika, Rieke; Mursiti, Titi; Amalia, Riza; Setiasih, Sri (Politeknik Kesehatan Kementrian Kesehatan Semarang, 2023)
Hyperbilirubinemia is one of the most common clinical phenomena in newborns, where hyperbilirubinemia occurs in 60% of Neonatus >35 weeks and 80% of Neonatus <35 weeks. Many factors influence hyperbilirubinemia. Hyperbilirubinemia if not handled properly can have serious consequences such as: kernicterus, chore athetoid cerebral palsy, hearing and cognitive impairment. This study aims to analyze the factors associated with the occurrence of hyperbilirubinemia and determine the relationship between breastfeeding, type of childbirth, birth weight, gestational age and asphyxia in infants at RSUD dr.Gunawan Mangunkusumo. This research is an analytical research with a cross sectional design. The sampling technique used total sampling, with a total of 52 infans as the sample size. Univariate data analysis was conducted using frequency distribution and bivariate analysis was performed using the chi-square test. The results of the univariate analysis showed that 65.4% of the infants with breastfeeding were fulfilled, 61.5% of action childbirth, 57.7% of normal birth weight, 53.8% of term gestational and 59.6% of asphyxia. There was a relationship between breastfeeding with a Ï-value of 0.014, there was no relationship with the types of childbirth with a Ï-value of 0.628, there was a relationship between birth weight and a Ï-value of 0.038, there was a relationship between gestational age with a Ï-value of 0.016, there was no relationship between asphyxia and a Ï-value 0.226 with the occurrence of hyperbilirubinemia. It is hoped that health workers will be more proactive in providing motivation and education to postpartum mothers and their families about breastfeeding and signs of hyperbilirubinemia symptoms as an effort to prevent and early detect hyperbilirubinemia